BOLD responses related to focal spikes and widespread bilateral synchronous discharges generated in the frontal lobe. (20th January 2015) - An, Dongmei; Dubeau, François; Gotman, Jean
Summary: Objective: To investigate whether specific frontal regions have a tendency to generate widespread bilateral synchronous discharges (WBSDs) and others focal spikes and to determine the regions most involved when WBSDs occur; to assess the relationships between the extent of electroencephalography (EEG) discharges and the extent of metabolic changes measured by EEG/functional magnetic resonance imaging (fMRI). Methods: Thirty‐seven patients with interictal epileptic discharges (IEDs) with frontocentral predominance underwent EEG/fMRI. Patients were divided into a Focal (20 patients) group with focal frontal spikes and a WBSD group (17 patients). Maps of hemodynamic responses related to IEDs were compared between the two groups. Results: The mean number ± SD of IEDs in the Focal group was 137.5 ± 38.1 and in the WBSD group, 73.5 ± 16.6 (p = 0.07). The volume of hemodynamic responses in the WBSD group was significantly larger than in the Focal group (mean, 243.3 ± 41.1 versus 114.8 ± 27.4 cm 3, p = 0.01). Maximum hemodynamic responses occurred in both groups in the following regions: dorsolateral prefrontal, mesial prefrontal, cingulate, and supplementary motor cortices. Maxima in premotor and motor cortex, frontal operculum, frontopolar, and orbitofrontal regions were found only in the Focal group, and maxima in thalamus and caudate only occurred in the WBSD group. Thalamic responses were significantly more common in the WBSD group (14/17) than in the Focal group (7/20), p = 0.004. Deactivation in the default mode network was significantly more common in the WBSD group (14/17) than in the Focal group (10/20), p = 0.04. Significance: The spatial distribution and extent of blood oxygen level–dependent (BOLD) responses correlate well with electrophysiologic changes. Focal frontal spikes and WBSDs are not region specific in the frontal lobe, and the same frontal region can generate focal and generalized discharges. This suggests that widespread discharges reflect widespread epileptogenicity rather than a focal discharge located in a region favorable to spreading. The thalamus plays an important role in bilateral synchronization.